Hubungan Pengetahuan dan Sikap Perawat dalam Penanganan Pertama Kondisi Syok Pasien DBD di Ruang Anak Rumah Sakit Swasta Bandung - Melya Florensisca Sinaga; Tina Shinta Parulian; Yuanita Ani (STIKes Santa Elisabeth Medan, 2021)
Background: Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus, causing plasma leakage so that it triggers hypovolemic shock. In July 2018, data obtained from one patient in the pediatric room died of shock (Dengue Shock Syndrome). Knowledge of shock management can prevent death. The purpose of the study was to determine the relationship between knowledge and attitudes of nurses in the first treatment of shock conditions of DHF patients in the children's room at the Bandung Private Hospital.Methods: This study uses a quantitative method with a descriptive correlational design through a cross sectional approach. Sampling using a total sampling obtained 89 respondents. Collecting data using a questionnaire to measure the relationship between knowledge and attitudes of nurses.Results: The results of the study obtained good knowledge of 74.2%, positive attitude 60.7%. Bivariate analysis using chi square test with p-value = 0.027 (p<α), shows a relationship between knowledge and attitudes of nurses in the first treatment of shock conditions in DHF patients.Conclusion: It is necessary to increase socialization and education in dealing with the shock condition of DHF patients so as to improve the quality of hospital services.